Efektivitas Restrukturisasi Pembiayaan akibat peningkatan Non Performing Finance (NPF) terdampak Covid-19 pada PT. Bank NTB Syariah - Hidayat Hidayat; Muslihun Muslim; Pongky Arie Wijaya (Universitas Bumigora, 2022)
The Covid-19 pandemic has had many negative impacts on the economic situation of the community. This study aims to explain the implementation of the restructuring of non-performing financing affected by Covid-19 at PT Bank NTB Syariah, explain the strategy undertaken by PT Bank NTB Syariah in the implementation of restructuring of non-performing financing affected by Covid-19, and to explain the obstacles faced and their solutions in implementing the restructuring problem financing. This type of research is a qualitative research, the research data obtained through in-depth interviews with several customers and employees of PT Bank NTB Syariah. The results of this study indicate that the restructuring by PT Bank NTB Syariah was given to customers who experienced problematic financing due to the impact of Covid-19. The strategy for implementing the restructuring carried out by PT Bank NTB Syariah is to provide two types of restructuring, namely rescheduling and reconditioning. Obstacles in the implementation of restructuring by PT Bank NTB Syariah during the Covid-19 pandemic, namely the bank's difficulty in conducting surveys to customers due to government policies in prohibiting outdoor activities and social interaction and the presence of customers who do not have the skills to make financial reports required by the bank as material for consideration before providing a restructuring policy.